Curability of solitary bone plasmacytoma - Dimopoulos, M.A.; Goldstein, J.; Fuller, L.; Delasalle, K.; Alexanian, R. (Journal of Clinical Oncology, 1992)
Purpose: The effects of involved-field radiotherapy were assessed in patients with a solitary plasmacytoma of bone (SBP). Patients and Methods: Forty-five consecutive patients with an SBP received megavoltage irradiation of at least 3,000 cGy. The median age was 53 years, 67% of patients showed a myeloma protein, and uninvolved immunoglobulins (Igs) were preserved in 93% of patients. Results: Permanent control of presenting disease was achieved in all but two patients, but 46% of patients developed multiple myeloma. When it occurred, progression of myeloma occurred within 3 years in two thirds of the patients, suggesting that the extent of disease was understaged at diagnosis. Myeloma protein disappeared in nine patients (30%) whose disease has not yet recurred. The median survival for all patients was 13 years and the myeloma- specific survival fraction at 10 years was 53%. Conclusion: In patients with an SBP, the disappearance of myeloma protein with involved-field radiotherapy predicted long-term disease-free survival and possible cure. Nonsecretory disease and persistent myeloma protein after treatment were adverse prognostic factors for which adjuvant therapy with interferon alfa should be considered.